THE IMPACTS OF ECONOMIC UNCERTAINTY ON INDONESIAN FIRMS’ TRADE CREDITS - Wennars, Lesely; Kim, Sung Suk (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract. This research was conducted with the aim of looking at the impact of economic uncertainty on short – term borrowing activities of Indonesian firms, especially on trade credit. The researcher uses quantitative research that includes a total of 7218 firm – year observations collected from 607 companies listed on IDX from 1998 to 2021. Using fixed effect panel data regression, the results show that there is a significant relationship between economic uncertainty and trade payables, trade receivables, and net credits. There was a decrease in trade payable during a crisis, on the other hand, an increase in trade receivables and net credit during years with a higher level of uncertainty. Abstrak. Penelitian ini dilakukan dengan tujuan untuk melihat dampak ketidakpastian perekonomian terhadap aktivitas pinjaman jangka pendek perusahaan-perusahaan Indonesia, khususnya pada kredit perdagangan. Peneliti menggunakan penelitian kuantitatif yang mencakup total 7218 observasi perusahaan – tahun yang dikumpulkan dari 607 perusahaan yang terdaftar di BEI dari tahun 1998 hingga 2021. Dengan menggunakan regresi data panel efek tetap, hasilnya menunjukkan bahwa terdapat hubungan yang signifikan antara ketidakpastian ekonomi dan utang usaha, piutang usaha, dan kredit bersih. Terjadi penurunan utang dagang pada saat krisis, sebaliknya terjadi peningkatan pada piutang dagang dan kredit bersih pada tahun-tahun dengan tingkat ketidakpastian yang lebih tinggi.